2012
DOI: 10.1007/s10928-011-9236-y
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan based indirect response models

Abstract: In the field of hematology, several mechanism-based pharmacokinetic-pharmacodynamic models have been developed to understand the dynamics of several blood cell populations under different clinical conditions while accounting for the essential underlying principles of pharmacology, physiology and pathology. In general, a population of blood cells is basically controlled by two processes: the cell production and cell loss. The assumption that each cell exits the population when its lifespan expires implies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Finally, also LSMs with distributed lifespans are recently introduced and applied, see [5] or [13]. An open question is, if for such models a similar relationship to TCMs holds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, also LSMs with distributed lifespans are recently introduced and applied, see [5] or [13]. An open question is, if for such models a similar relationship to TCMs holds.…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan models (LSM) are important tools to describe the development of a population y(t) controlled by birth (input) and death (output) of their individuals. For an overview of LSMs in the context of indirect response models see [5]. LSMs have the general form y 0 ðtÞ ¼ k in ðtÞ À k out ðtÞ; yð0Þ ¼ y 0…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the IL-6 pathway is involved in T-cell activation and stimulation of hematopoiesis: the blockade of IL-6 receptor triggers not only a reduction in systemic inflammation, but also mechanism-related adverse effects, including a decrease in neutrophil and platelet counts. A mechanistic model, which included TMDD and lifespan models [114], showed that the decrease in neutrophil and platelet counts were concentration dependent and was reversible when tocilizumab was withdrawn [35]. To date, no concentration-adverse effect relationship was reported for anti-TNF-a biopharmaceuticals.…”
Section: Concentration-adverse Effect Relationshipsmentioning
confidence: 99%
“…Indirect models are lifespan-based compartmental PK/PD models (e.g., lifespan-based indirect response or LIDR models [38]), of which transit compartment (TC) models are a special case [37]. A series of transit compartments, each compartment with a PDF representing the lifespan distribution of the cells in that compartment [30, 37, 45] is a hallmark of TC models.…”
Section: Introductionmentioning
confidence: 99%
“…A new lifespan based compartmental PK/PD model paved the way to an indirect and compartmental approach to quantify RBC/reticulocyte mean lifespan [39]. Earlier works based on this approach assumed that all cells in a compartment survived for a fixed time, which introduced a time-delay in the input/output models thus representing the lifespan of the cells in a compartment by a point distribution [1, 38, 39, 41, 57, 59]. The theory was expanded later to represent the RBC lifespan distribution by possibly time-varying continuous PDF [2123, 40, 61].…”
Section: Introductionmentioning
confidence: 99%